The Importance of Emotional Intelligence in Teachers: A Systematic Literature Review - Simon Petrus (Universitas Negeri Semarang, 2021)
A teacher's emotional intelligence has a very important role in the world of education (Ignat and Clipa, 2012). The purpose of this research is to study the benefits and factors as well as an understanding of teachers' emotional intelligence. The method used is systematic literature review. Article searches were conducted on Eric, Science Direct, Proquest, the Wiley Online Library and Taylor & Francis. using an online search engine using the keyword “teacher's emotional entelligent” A total of 6 articles in the 2015-2020 period were found to be appropriate and were used to conduct a systematic literature review. The literature review found that teachers with a higher level of emotional intelligence provide the ability to manage and regulate emotions which will improve teacher performance in performing their duties. The results of this review study can be used by other researchers who are interested in researching and developing the theory of emotional intelligence, especially its relation to the development of the quality of education in schools.